Frequency of Cirrhotic Cardiomyopathy Among Patients with Liver Cirrhosis - Baig, Mirza Muhammad Usman; Malik, Kashif; Jahangir, Sundus; Aslam, Muhammad; Shah, Firasat; Abdul Haq,; kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Introduction: Patients with liver cirrhosis may develop cirrhotic cardiomyopathy (CCM), a disorder marked by a compromised cardiac response to stress. Because of its mild clinical appearance and comorbidity with other signs of liver disease, it often remains undetected. The purpose of this study is to evaluate the clinical importance of CCM and ascertain its prevalence in cirrhotic individuals. Methods: Study was conducted from July 2024 to December 2024. Purposive sampling was used to identify 200 liver cirrhosis patients from a tertiary care hospital in Karachi, Pakistan, for this qualitative study. Semi-structured, in-depth interviews were used to gather data, and thematic analysis was used to find recurrent themes in the participants' CCM experiences. Results: According to the study, patients with cirrhosis that lasted one to three years had the highest prevalence of CCM symptoms, with fatigue and dyspnea being the most often reported symptoms. Significant abnormalities were revealed by echocardiography, including an enlarged left atrium and left ventricular diastolic dysfunction. The majority of individuals reported symptoms after 1-3 years of cirrhosis, and the frequency of CCM symptoms rose with the length of cirrhosis. Conclusion: The prevalence of cirrhotic cardiomyopathy (CCM) in clinical practice is significant, as highlighted by this study. Findings emphasize the link between cirrhosis duration and CCM onset, with myocardial dysfunction worsening as cirrhosis progresses. Common symptoms include peripheral edema, fatigue, and dyspnea. Echocardiography often reveals left atrial enlargement and ventricular diastolic dysfunction. Early detection and cardiovascular monitoring, especially in decompensated cirrhosis, can reduce morbidity and mortality through timely intervention.